Elective Course for Medical Students: Topicality, Development, Implementation, Benefits - Koka, Rudīte; Tatjana Koķe; Juta Kroiča; Linda Meškovska (European Journal of Social Science Education and Research, 2024)
A growing trend in Latvia’s healthcare is patients’ choice to use phytotherapy alongside pharmaceutical drugs both as a preventive measure and means of therapy for various diseases. A number of medical students of the Faculty of Medicine at R?ga Stradi?š University (hereinafter – RSU) plan to become general practitioners in the future. These specialists should have an overall understanding of phytotherapy, skills to evaluate its effects on the body and possible side effects in order to professionally advise and give suggestions to their patients. Therefore an innovative elective course Medicinal Plants and Their Use was introduced in the curriculum of the Medicine programme in 2011. In order to be chosen by the students the course must correspond to the highest quality standards. Important aspects of quality are the evaluation of implementation and perfection. The university by involving students in the content creation of elective courses promotes the belonging of students, extends the range of courses, develops maximum practical benefit of students and is able to ensure high quality of education. The article summarizes the experience in developing the elective course, analyses its implementation, evaluation and perfection as well as benefits for medical students.